Brazilin From Caesalpinia sappan L. Induced Apoptosis via mTOR and HO-1 Pathway in SW480 Human Colon Cancer Cells - Hong, On-Yu; Cho, Eugene; Kim, Jong-Suk; Park, Kwang-Hyun (Frontiers in Energy Research, 2022)
The mTOR pathway is a crucial biological regulatory mechanism of cell growth, proliferation and cell death, and its inhibitors were new candidates of anticancer drugs through regulation of energy balance and metabolism. In the present study, whether brazilin and mTOR inhibitor (Torin1) exerts anti-cancer effects was evaluated and the mechanism of its regulation in colorectal cancer cells investigated. Brazilin showed dose- and time-dependent cytotoxicity of colorectal cancer cells (SW480 cells) through apoptosis pathways such as Bcl-2, Bax, as well as cleavage of caspase 3, caspase 9, and PARP1. In addition, brazilin reduced mammalian target of rapamycin (mTOR) phosphorylation in a dose- and time-dependent manner, and the mTOR inhibitor torin 1 blocked this phosphorylation. Brazilin also decreased heme oxygenase-1 (HO-1) expression in a dose- and time-dependent manner; however, hemin, a specific HO-1 substrate, markedly increased HO-1 expression. Torin 1 reduced hemin-induced HO-1 expression and increased colorectal cell death in a dose-dependent manner in the presence and absence of hemin. Moreover, nuclear factor erythroid 2–related factor 2 (Nrf2) translocation into nucleus fraction was crucial role in brazilin-mediated apoptosis of colorectal cancer cells. These results showed that brazilin and torin1 might regulate the mTOR signaling pathway by decreasing mTOR phosphorylation. Furthermore, mTOR signaling was associated with brazilin-regulated HO-1 expression, which induced apoptosis in colorectal cancer cells. These results suggest that synthetic and/or natural mTOR inhibitors were useful candidate for treatment of colorectal cancer cells.